Mobilising situated local knowledge for participatory urban planning through storytelling - Seydel, Hanna; Huning, Sandra (Technische Universität Dortmund, 2022)
Participatory urban planning does not take place outside of social systems of privilege and discrimination; likewise, the negotiation of knowledge claims in planning processes is embedded in social relations defined by “gender,” “race,” and “class.” In this article, we argue that positionalities play out in the social construction of knowledge in participatory planning and that, consequently, a certain type of knowledge—typically represented by well-educated and resourceful residential groups—is privileged over other forms of everyday knowledge. We present storytelling as an inclusive approach to co-producing knowledge and reflecting on the extent to which the findings can be applied to participatory urban planning. This article is based on a three-year inter- and transdisciplinary research project based on real-world laboratories in two German neighbourhoods. Regarding feminist geographies, we first explore the role of power, positionality, and situated knowledge in shaping participatory planning, both theoretically and empirically. We outline the extent to which the methodological framework and the socio-spatial setting have an impact on the co-production of knowledge. We present insights from two storytelling interventions and reflect on the possibilities and limits of narrative knowledge production for participatory urban planning.
Urban planning;7(3)
Keywords: Participation; Positionality; Power relations; Situated knowledge; Storytelling; 710; Partizipation; Storytelling; Stadtplanung